Scientific Opinion updating the evaluation of the environmental risk assessment and risk management recommendations on insect resistant genetically modified maize 1507 for cultivation - EFSA Panel on Genetically Modified Organisms (GMO) (Wiley, 2011)
Abstract In this Scientific Opinion, the EFSA GMO Panel supplements its previous evaluations of the potential impact of maize 1507 cultivation on a range of non‐target lepidopteran species using existing data on species susceptibility and considering various scenarios of exposure which may occur across Europe. The mathematical model, developed for maize MON 810, was recalibrated and extended to estimate the efficacy of certain mitigation measures. In situations where highly sensitive non‐target Lepidoptera populations might be at risk, the EFSA GMO Panel recommends that mitigation measures are adopted to reduce exposure. Risk managers are provided with tools to estimate global and, where needed local, mortality of exposed non‐target Lepidoptera, both before and after different mitigation measures are put in place, and for different host‐plant densities. Mitigation measures are only needed when the proportion of maize and uptake of maize 1507 are sufficiently high, regardless of the other parameters. If maize 1507 cultivation remains below 5% of the Utilized Agricultural Area, then risk mitigation measures are not required. In addition, the EFSA GMO Panel recommends case‐specific monitoring to assess the efficacy of risk mitigation measures put in place to reduce levels of risk and scientific uncertainty for (1) the possible resistance evolution to the Cry1F protein in target pests, and (2) the risk to sensitive non‐target Lepidoptera from maize 1507 pollen. The EFSA GMO Panel also considers that the plan for general surveillance, and in particular the methodology, needs further details according to the requirements of its 2011 Guidance Document on post‐market environmental monitoring of generically modified plants, as well as its Scientific Opinion on the annual 2009 monitoring report on maize MON 810. The EFSA GMO Panel concludes that, subject to appropriate management measures, maize 1507 cultivation is unlikely to raise safety concerns for the environment.